A Grammatical Analysis of Conjunction Usage in Student Vlog Assignments from the Mündliche Konversation Course at Universitas Negeri Malang - Pangesti, Isnaini Nur; Faulanita Pawittri Trisnawati; Iwa Sobara (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This research aims to describe the use of conjunctions by third-semester students of the German Language Education program at Universitas Negeri Malang in their oral communication tasks in the form of vlogs, and to identify the grammatical errors present in their usage. These vlogs are outputs of the course Mündliche Konversation, which is designed to train students' speaking skills in a realistic, independent, and communicative context. This study employs a qualitative approach using content analysis methods. Data were collected from the documentation of eight group videos created by students and analyzed based on German grammar theory by Helbig and Buscha (1996). The results show that students used various types of conjunctions, both coordinating and subordinating, with a predominance of subordinating conjunctions such as dass and weil. Despite attempts to construct complex sentence structures, several errors were found, including errors in verb placement, verb selection, absence of a subject, and the lack of a verb in clauses, indicating the need for further grammatical development.